Treatments after second progression in metastatic colorectal cancer: A pooled analysis of the TRIBE and TRIBE2 studies. (July 2022) - Rossini, Daniele; Germani, Marco M.; Lonardi, Sara; Pietrantonio, Filippo; Dell'Aquila, Emanuela; Borelli, Beatrice; Allegrini, Giacomo; Maddalena, Giulia; Randon, Giovanni; Marmorino, Federica; Zaniboni, Alberto; Buonadonna, Angela; et al.
Abstract: Background: The availability of new drugs in the chemo-refractory setting opened the way to the concepts of treatment sequencing in mCRC. However, the impact of later line options in the therapeutic route of metastatic colorectal cancer (mCRC) patients and the attrition rate across subsequent lines of therapy are not well established. Methods: We performed a pooled analysis of treatments administered after the 2nd disease progression in 1187 mCRC patients enrolled in the randomized phase III TRIBE and TRIBE2 studies, where upfront FOLFOXIRI/bev was compared with FOLFOX or FOLFIRI/bev. Per each line, we assessed the attrition rate, treatment choices and clinical outcomes. Results: 625 (53%), 326 (27%) and 136 (11%) patients received a systemic treatment after the 2nd, 3rd and 4th disease progression, respectively. PFS and objective response rate decreased along each line. RAS/BRAF wild-type patients received more likely a 3rd line (75%) compared with RAS (66%, p = 0.005) and BRAF (66%, p = 0.11) mutants. In 3rd line, 67% of RAS/BRAF wild-type patients received anti-EGFRs, achieving longer PFS with respect to other therapies (6.4 vs 3.9 months, p = 0.02). A trend towards longer 3rd line OS was observed in TRIBE patients (9.9 vs 7.2 months, p = 0.05). Conclusions: A relevant attrition rate across subsequent lines of therapy is evident, and more pronounced in RAS and BRAF mutated patients, thus highlighting the relevance of the choice of the upfront treatment. The efficacy of anti-EGFR agents among RAS/BRAF wild-type patients unexposed to anti-EGFRs is higher than other options. The reintroduction of chemotherapy remains frequent in clinical practice. Trial registration: Clinicaltrials. gov Identifiers NCT00719797, NCT02339116. Highlights: 53% of mCRC patients treated with upfront doublets/triplet + bev receive a 3rd line. RAS/BRAF wild-type patients achieve more likely a 3rd line versus RAS/BRAF mutants. In 3rd line, RAS/BRAF wild-type patients reach longer disease control with anti-EGFRs. Regorafenib and Tas-102 show modest efficacy, and chemotherapy re-challenge is frequent. The pronounced funnel effect in BRAF mutants endorses early blockade of BRAF + EGFR.